ANALISA PENGARUH COST LEADERSHIP, DIFFERENTATION STRATEGY DAN MARKET ORIENTATION TERHADAP KINERJA PERUSAHAAN - Purwianti, Lily (Journal of Global Business and Management Review, 2019)
The main purposes of this  study is  to analyze the relationship of cost leadership, differentiation strategy, market orientation and organization performance.  The research sample are souvenirs shop in Batam City. Multiple regression analysis to test the hypothesis. The results of this study are information about cost leadership, differentiation strategies, market orientation towards company performance. The results showed that cost leadership, differentiation strategy, market orientation has significant efect on organization performance.